(The Effect of ImplementationofInteractive Multimedia with Learning Inquiry on Equilibrium Solusiontoward chemistry student’s achievement) - Febliza, Asyti (UIR Press, 2018)
The Using of method and media precisely in learning process affect to student’s achievement. The purpose of this study is to determine: Is there any influence in using interactive multimedia with inquiry on equilibrium solusion topic toward chemistry student’s achievement. The population of this study were all chemistry student in first level in Faculty of Teacher Department of Universitas Riau (UR). The sample in this research were nonreguler chemistry students in first level of chemistry education department UR academic year 2010/2011 with total number 76 students which divided into 2 classes. The instrument that was used to collect data was cognitive test questions about 20 item. The hypothesis was analyzed by General Linear Model (GLM) Univariate, SPSS 17.0.The results of hypothesis analysis could be concluded that: (1) There was the influence in using interactive multimedia with inquiry on equilibrium solusion topic toward chemistry student’s achievement with level of significant (p = 0.000).